Tuning the Dimensions of C 60 ‐Based Needlelike Crystals in Blended Thin Films - Swinnen, A.; Haeldermans, I.; vande Ven, M.; D'Haen, J.; Vanhoyland, G.; Aresu, S.; D'Olieslaeger, M.; Manca, J. (Advanced functional materials, 2006)
A new ordered structure of the C 60 derivative PCBM ([6‐6]‐phenyl C 61 ‐butyric acid methyl ester) is obtained in thin films based on the blend PCBM:regioregular P3HT (poly(3‐hexylthiophene)). Rapid formation of needlelike crystalline PCBM structures of a few micrometers up to 100 μm in size is demonstrated by submitting the blended thin films to an appropriate thermal treatment. These structures can grow out to a 2D network of PCBM needles and, in specific cases, to spectacular PCBM fans. Key parameters to tune the dimensions and spatial distribution of the PCBM needles are blend ratio and annealing conditions. The as‐obtained blended films and crystals are probed using atomic force microscopy, transmission electron microscopy, selected area electron diffraction, optical microscopy, and confocal fluorescence microscopy. Based on the analytical results, the growth mechanism of the PCBM structures within the film is described in terms of diffusion of PCBM towards the PCBM crystals, leaving highly crystalline P3HT behind in the surrounding matrix.